THE STATUS OF LOCAL REPRESENTATIVE BODIES IN KAZAKHSTAN AND OTHER POST-SOVIET COUNTRIES THAT STEPPED ON THE PATH TO DECENTRALIZATION: A COMPARATIVE ANALYSIS (Lex localis - Journal of Local Self-Government, 2025)
This study aims to explore the similarities and differences between the status and powers of local representative bodies in Kazakhstan and two other post-Soviet countries– Ukraine and Georgia. The findings will make it easier to grasp the challenges that Kazakhstan faces when building an effective system of local self-government. The results show that despite the shared post-Soviet past, the studied countries have chosen different trajectories for decentralization and have been implementing their reforms at different pace. The instruments to promote citizens’ participation have been formalized in all three countries, creating the necessary foundation to further decentralization efforts.